Prevalence of sleep problems and its relation to sleeping habits in toddlers - Maree, Sima; Mohammadi Zidi, Esa; Yari, Saeed; Javadi, Maryam (Asian Pacific Journal of Environment and Cancer, 2019)
Background: Sleep problems in children have serious physical and psychological consequences such as obesity, aggression and attention deficit disorder in toddlers. The aim of the present study was to determine the prevalence of sleep problems and its relation with sleeping habits of toddlers in 2017. Methods: By random sampling from rural families of Razan city of Hamadan province, 120 mothers of 12- to 36-month-old children were selected and data collection tools included contextual questions, medical history and 33-question questionnaire of children’s sleep habits (CSHQ) completed. Data were analyzed by SPSS software version 23, independent t-test, chi-square, Pearson correlation coefficient and multiple linear regression. Results: The mean age of the children was 22.82±7.53 months and 55% of them were boys and the prevalence of sleep problems was 70.8% (95% confidence interval: 71.9-69.7). The average sleep duration of the children was 11 hours and more than 60% of the children went to bed after 23 o’clock. Results show that age is an important factor in most dimensions of CSHQ and age predicts daytime sleepiness (β = -0.263), nocturnal wakefulness (β = -0.113) and duration, Sleep time (β = -0.108) and sleep resistance (β = 0.194) respectively. Also, parents’ education and child’s current weight were predictors of subscales of CSHQ questionnaire (P <0.05). In addition, there was a positive and significant correlation between sleep duration with infant sleep anxiety (r = 0.527) and resistance to sleep (r = 0.473) as well as nocturnal wakefulness with parasomnia (r = 0.416) (P <0.001). Conclusion: Given the alarming prevalence of sleep problems in toddlers in the present study and the impact of some changeable factors on children’s sleep health, designing interventions aimed at educating mothers to improve healthy sleep habits in toddlers is necessary.